State crime = Staatskriminalität - Ruggiero, Vincenzo (Kriminologisches Journal, 2023)
Definitions evolve and are often unable to catch up with the actions they attempt to describe. The following pages intend to convey the definitional uncertainty that surrounds state crime, its ever-changing nature and the permanent difficulties we encounter when trying to grasp its definite features.